2012
DOI: 10.1007/s11661-012-1205-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Boron on Carbide Coarsening at 873 K (600 °C) in 9 to 12 pct Chromium Steels

Abstract: The addition of small amounts of boron to 9 to 12 pct chromium steels has been found to decrease their creep rate at 823 K to 923 K (550°C to 650°C). In this article, the behavior of boron during austenitizing, tempering, and isothermal heat treatment at 873 K (600°C) is studied using high-resolution microscopy and microanalysis as well as using atomistic modeling. It was found that increasing the boron content from 9 to 40 ppm decreased the coarsening constant of M 23 C 6 by a factor of almost 2. Most of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(32 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…An alternative approach is to tailor the characteristics of such potentially detrimental phases by adding some other alloying elements in order to slow down the coarsening. In the literature, it has been reported that the coarsening rate of M 23 C 6 can be decreased moderately by adding B, Co, or W. [6][7][8][9][10] Abe [11,12] reported that the coarsening rate of Laves phase can also be effectively reduced by substituting W for Mo. The shape of W-enriched Laves phases is also near spherical, which is more coherent and stable than needle-shaped precipitates.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach is to tailor the characteristics of such potentially detrimental phases by adding some other alloying elements in order to slow down the coarsening. In the literature, it has been reported that the coarsening rate of M 23 C 6 can be decreased moderately by adding B, Co, or W. [6][7][8][9][10] Abe [11,12] reported that the coarsening rate of Laves phase can also be effectively reduced by substituting W for Mo. The shape of W-enriched Laves phases is also near spherical, which is more coherent and stable than needle-shaped precipitates.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 9%~12%Cr martensitic heat resistant steels with good creep properties, high thermal conductivity coefficient and low thermal expansion coefficient have been widely used in ultra-supercritical (USC) coal-fired power plants, especially in the thick wall section [1][2][3][4][5][6][7]. With increasing the steam temperature from 600 ºC to 650 ºC, traditional martensitic heat resistant steels such as P91, P92 and P122 [7][8][9][10] cannot satisfy the more demanding requirement any more.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the creep rate can be decreased. In the work of and Liu et al (2012), boron was found to be able to effectively decrease the coarsening rate of M 23 C 6 carbides by forming M 23 (C,B) 6 . Consequently, they have successfully developed a new boron containing steel, 9Cr3W3CoB, based on the chemical composition of 9Cr3W3Co.…”
Section: Boron Containing 9cr3w3cob Steelmentioning
confidence: 98%